Liver damage due to perhexiline maleate. - Forbes, G B (1979)
Two middle-aged men, who had received perhexiline in recommended dosage, showed clinical and histological evidence of severe hepatic damage, and one of them died. Histological study of the livers showed a striking resemblance to alcoholic hepatitis.